The Development of a prebiotic probiotic ice cream in Usaha Bersama Tani Ternak joint business group, Tadukan Raga Village, STM Hilir Regency, Deli Serdang County - nurzainah ginting; Armansyah Ginting; Mirwandhono R. Edhy; Zuhrina Masythah (Journal of Saintech Transfer, 2025)
The focus of the service was teaching at the Usaha Bersama Tani Ternak Joint Business Group, Tadukan Raga Village, STM Hilir District, Deli Serdang Regency. In this group, many dairy goat farmers produce milk. Product innovation from goat milk is needed because, if we rely solely on the basic product — milk — there are limitations for consumers who buy it. In 2023, in the Joint Business group, training was conducted to make ice cream from goat's milk. The innovation of processing milk into ice cream will expand the product's marketing range and increase its shelf life. In 2024, assistance was provided to this group to develop ice cream with prebiotic and probiotic innovations. This is a regular one-year service, carried out in July 2024, and assistance will continue until December 2024. It is hoped that after the service, processing goat's milk into ice cream will be carried out intensively. Given that the air in North Sumatra is getting hotter, ice cream products will be in high demand. In addition, this community service activity also improves the Main Performance Indicators (IKU) of Higher Education, namely IKU 2, 3, and 5.  Mandatory outputs of this community service activity program include: 1) Scientific publications in abdimas journals/service journals with ISSN / National Journal Proceedings, 2) videos, and 3) disseminated through electronic/print media. Additional outputs include the production of probiotic prebiootic ice cream and participation in a national seminar, as well as the development of probiotic prebiotic ice cream products in Deli Serdang Regency.